Pengaruh Biaya Promosi, Biaya Pendidikan dan Pelatihan Terhadap Pembiayaan UMKM Pada Bank Pembiayaan Rakyat Syariah Periode 2019-2023 - Rismawati, Riri; Nurhasanah, Elis (Islamic Economics and Business Review, 2024)
Abstract Sharia People's Financing Banks (BPRS) have several cost components that can influence the amount of financing distributed to MSMEs, namely promotional costs, education and training costs. However, in the 2019-2023 period, Sharia People's Financing Banks (BPRS) experienced fluctuations in promotional costs, education and training costs which may have a direct impact on the financing distributed to MSMEs. The aim of this research is to determine and analyze the influence of Promotion Costs, Education and Training Costs on MSME Financing at Sharia People's Financing Banks for the 2019-2023 period. The analysis used uses descriptive statistical analysis, multiple linear regression analysis, analysis of the coefficient of determination (R2), and hypothesis testing using the t test and F test. The results of this research show that partially promotional costs have a positive and significant effect on MSME financing. Meanwhile, education and training costs do not have a positive and significant effect on MSME financing at Sharia People's Financing Banks (BPRS) for the 2019-2023 period. And simultaneously promotion costs and education and training costs have an influence on MSME financing at Sharia People's Financing Banks (BPRS) for the 2019-2023 period.   Keywords: Promotion Costs; Education and Training Costs; MSMEs Abstrak Bank Pembiayaan Rakyat Syariah (BPRS) memiliki beberapa komponen biaya yang dapat mempengaruhi jumlah pembiayaan yang di salurkan kepada UMKM yakni biaya promosi, biaya pendidikan dan pelatihan. Namun, dalam kurun waktu 2019-2023 Bank Pembiayaan Rakyat Syariah (BPRS) telah mengalami fluktuasi dalam biaya promosi, biaya pendidikan dan pelatihan yang mungkin berdampak langsung terhadap pembiayaan yang di salurkan kepada para UMKM. Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis pengaruh dari Biaya Promosi, Biaya Pendidikan dan Pelatihan Terhadap Pembiayaan UMKM pada Bank Pembiayaan Rakyat Syariah Periode 2019-2023. Analisis yang digunakan menggunakan analisis statistik deskriptif, analisis regresi linier berganda, analisis koefisien  determinasi (R2), serta pengujian hipotesis dengan uji t dan uji F. Hasil penelitian ini menunjukan bahwa secara parsial biaya promosi berpengaruh positif dan signifikan terhadap pembiayaan UMKM. Sedangkan biaya pendidikan dan pelatihan tidak berpengaruh positif dan signifikan terhadap pembiayaan UMKM pada Bank Pembiayaan Rakyat Syariah (BPRS) periode 2019-2023. Dan secara simultan biaya promosi dan biaya pendidikan dan pelatihan memiliki pengaruh terhadap pembiayaan UMKM pada Bank Pembiayaan Rakyat Syariah (BPRS) periode 2019-2023. Kata kunci: Biaya Promosi, Biaya Pendidikan dan Pelatihan, UMKM